A novel linear neutralizing epitope of hepatitis E virus. Issue 30 (9th July 2015) - Tang, Zi-Min; Tang, Ming; Zhao, Min; Wen, Gui-Ping; Yang, Fan; Cai, Wei; Wang, Si-Ling; Zheng, Zi-Zheng; Xia, Ning-Shao
Highlights: A novel neutralizing epitope L2 of HEV was identified. The novel epitope is located in a.a. 423–437 of HEV pORF2. Epitope L2 is non-immunodominant in both infection and vaccination process. We displayed epitope L2 on HBc149 protein and constructed HBcL2 particles. Immunization with HBcL2 stimulated anti-HEV neutralization in vivo . Abstract: Hepatitis E virus (HEV) is a serious public health problem that causes acute hepatitis in humans and is primarily transmitted through fecal and oral routes. The major anti-HEV antibody responses are against conformational epitopes located in a.a. 459–606 of HEV pORF2. All reported neutralization epitopes are present on the dimer domain constructed by this peptide. While looking for a neutralizing monoclonal antibody (MAb)-recognized linear epitope, we found a novel neutralizing linear epitope (L2) located in a.a. 423–437 of pORF2. Moreover, epitope L2 is proved non-immunodominant in the HEV-infection process. Using the hepatitis B virus core protein (HBc) as a carrier to display this novel linear epitope, we show herein that this epitope could induce a neutralizing antibody response against HEV in mice and could protect rhesus monkeys from HEV infection. Collectively, our results showed a novel non-immunodominant linear neutralizing epitope of hepatitis E virus, which provided additional insight of HEV vaccine.